Investigation of the pyrolysis and gasification of a Turkish coal using thermal analysis coupled with mass spectrometry - (:unkn) unknown (My University, 2010)
Clean conversion of coal into gaseous and liquid fuels and chemicals is of utmost importance along with its direct utilization via combustion in a sustainable manner. Pyrolysis is an important intermediate stage in coal conversion processes such as combustion and gasification. Coal gasification is applied in IGCC systems for power generation as well as for the production of a range of gaseous and liquid fuels from hydrogen to diesel. Thermal analysis results coupled with mass spectrometry (TA/MS) applied to the pyrolysis and gasification of a Turkish coal are presented here. Pyrolysis experiments have been carried out in argon atmosphere while air has been used as the gasification agent. The samples have been heated from room temperature up to 1000°C. The main evolved products have been identified through the on-line recorded mass spectra. The thermolysis behavior of the coal sample has been checked comparatively for selected gas flow rates and heating rates. The gas flow rate has been changed between 5 and 70 mL/min whereas the heating rate range has been selected as 10 to 40 °C/min. Two different sample masses (5 and 10mg) have been used to observe any effect of the mass on the thermal analysis results. Final operation conditions are based on these results. The TG curves, the on-set, shape and off-set of the DTG curves combined with the evolution temperatures of the major gaseous products such as H2, CO, CO 2, CH4, H2S and SO2 for the selected appropriate operation conditions clearly show differences in the thermolysis behavior at different atmospheres, gas flow rates and heating rates. These differences in thermolysis behavior indicate when and under which conditions pyrolysis and/or partial oxidation (gasification) and/or oxidation might be occurring. The TAMS results are also indicative of the reactivity of the coal sample to the selected atmosphere at various temperatures. TG-MS results can be utilized to determine kinetic parameters via various methods. Care should be taken to avoid mass transfer limitations. The results prove that the gasification of coal consists of two major reactions: pyrolysis and gasification of in situ formed char. The rate of the latter reaction is much slower than that of the former reaction. The volume of the gasifier is therefore primarily dependent on the gasification rate of char. For this reason, kinetics of char gasification obtained by TA/MS plays a key role by providing valuable information for the proper design and operation of gasifiers.